The impact of drugs, infants, single mothers, and relatives on reunification: A Decision-Making Ecology approach. (November 2015) - Wittenstrom, Kim; Baumann, Donald J.; Fluke, John; Graham, J. Christopher; James, Joyce
Abstract: Using a Decision-Making Ecology (DME) approach and proportional hazards models, the study isolated four case factor profiles that interacted strongly with race and resulted in disparate reunification outcomes for African American children compared with Anglos. The four interrelated factors were drug involvement, a solo infant case, single mothers, and relative placements. A cohort of 21, 763 children from the Texas Department of Family and Protective Services who were placed for the first time in care, who were under 13 and either Anglo or African American were followed for 20 months or more post entry into care. Starting with an initial model consisting of main effects only and consistent with other studies, African American children had a 12% lower hazard rate of reunification compared to Anglo children. However, when a set of case profiles involving combinations of single parents, single infants, drug involvements and kinship placements were crossed with race, the magnitude of the effect of race on hazard rates fanned out from no difference to as much as 68% that of Anglo children. The results show that racial disparities in outcomes resulting from complex, contextual decision making cannot be modeled well with simple main effects models.